Spectral dependence of the photomagnetic effect in porous silicon - Vakulenko, O.V.; Kondratenko, S.V.; Serdega, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Measurements of the photomagnetic effect spectra of PS/c-Si were carried out. Obtained results were explained by influence of the spatial charge region of the heterojunction between wide-band porous silicon and c-Si substrate of the n-type. The form of the PME spectrum in the long-wave region indicates to the drift of the nonequilibrium charge carriers in the c-Si to the PS/c-Si boundary, that is presence of the increased spatial charge layer in c-Si. Relatively high value of the PME in the strong absorption region of the porous silicon indicates to the presence of the PME component caused by porous silicon material.